MATERNAL FACTORS ASSOCIATED WITH CESAREAN SECTION IN INDONESIA: EVIDENCE FROM IDHS 2017 - Istiqomah Risa Wahyuningsih; Hartono Hartono; Vitri Widyaningsih; Sri Mulyani (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Introduction: Increased the number of cesarean sections in Indonesia based on IDHS data in 2017 by 17.6%. This figure exceeds the recommendation of WHO, which is 10-15%. The impact of cesarean section related to maternal and infant health, health financing budgets, and public health policies. This research article analyzes the relationship between maternal factors and cesarean section in Indonesia. This is a novelty in this article. Objective: This article aims to analyze the relationship of maternal factors with cesarean section in Indonesia. Method: The design of this study is a cross-sectional study using data from the 2017 Indonesian Demographic and Health Survey (IDHS). The sampling design was stratified two-stage sampling, with a sample of 14,891 respondents. Data was analyzed using Stata 14.2. Data were analyzed using univariate analysis, bivariate analysis multivariate analysis. Results: Women who experienced pregnancy complications had a 1.2 times greater risk of cesarean section (OR=1.2, CI=1.0-1.4). Women who had a history of cesarean section had a 64.8 times greater risk of having a cesarean section (OR = 64.8, CI = 38.2-109.9). While the variables of labor complications, twins, and pregnancy spacing had no effect on cesarean section (OR<1). Conclusion: Monitoring and evaluation of the increasing number of cesarean sections without medical indication and the severity of labor is necessary. The decision to undergo a cesarean section should be based on clear and solid reasons, supported by good medical data.